Identification of research gap: T-commerce impulse purchase for iTV advertising - Che Omar, Azizah; Shiratuddin, Norshuhada; Sarif, Siti Mahfuzah; Abdul Mutalib, Ariffin; Mohd Rashid, Sabrina (2013)
iTV advertising provides consumers with new sales channels as well as gives higher return to the advertisers.T-commerce is a tool in iTV advertising that enables users to buy something directly through television screen which is more flexible, comfortable, and convenient.Studies show that there is a necessity to examine the factors influencing individuals to purchase products on television shopping program.However, research effort on this is minimal.Also, design models that are dedicated to increase impulse purchase on iTV advertising are scarce and do not include consumer behaviour regarding impulse purchase.In fact, research on the design of t-commerce for iTV advertising for effective marketing strategies is still lacking.Therefore, such a gap ought to be investigated which could contribute to the fields of business and interactive advertising.